2023
DOI: 10.1111/edt.12844
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of emergency department physicians regarding the management of traumatic dental injuries

Abstract: Background/AimThe purpose of this study was to investigate the self‐reported confidence level and education of Atlantic Canada emergency department physicians in the management of traumatic dental injuries and to assess the need for further education surrounding the management of dental trauma.Material and MethodsAn 18‐item survey was developed and distributed electronically to physicians by their respective provincial medical associations.ResultsTraumatic dental injuries were reported in the emergency departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…33 In this Issue, Steeves et al investigated the self-reported confidence level and education of Atlantic Canada ED physicians and assessed the demand for further training on the management of traumatic dental injuries (TDIs) and the most preferable method to provide this training. 34 An 18 multiple-choice or ranking question survey was employed to assess demographics, education and self-reported confidence, and demand for further education regarding TDIs management. Although dental care is ideally provided by dental personnel, ED physicians are in a unique position to support patients until they can access the timely dental care required.…”
Section: Predictive Factors For Maxillofacial Fractures Sedentary Beh...mentioning
confidence: 99%
See 1 more Smart Citation
“…33 In this Issue, Steeves et al investigated the self-reported confidence level and education of Atlantic Canada ED physicians and assessed the demand for further training on the management of traumatic dental injuries (TDIs) and the most preferable method to provide this training. 34 An 18 multiple-choice or ranking question survey was employed to assess demographics, education and self-reported confidence, and demand for further education regarding TDIs management. Although dental care is ideally provided by dental personnel, ED physicians are in a unique position to support patients until they can access the timely dental care required.…”
Section: Predictive Factors For Maxillofacial Fractures Sedentary Beh...mentioning
confidence: 99%
“…In order to achieve better treatment outcomes, dental education for physicians should be enhanced 33 . In this Issue , Steeves et al investigated the self‐reported confidence level and education of Atlantic Canada ED physicians and assessed the demand for further training on the management of traumatic dental injuries (TDIs) and the most preferable method to provide this training 34 . An 18 multiple‐choice or ranking question survey was employed to assess demographics, education and self‐reported confidence, and demand for further education regarding TDIs management.…”
mentioning
confidence: 99%